Modulation of Human Neutrophil Responses by the Essential Oils from Ferula akitschkensis and Their Constituents; Journal of Agricultural and Food Chemistry; Vol. 64, № 38 - Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Kushnarenko S. V. Svetlana; Ozek G. Gulmira; Kirpotina L. N. Liliya Nikolaevna; Sinharoy P. Pritam; Utegenova G. A. Gulzhakhan; Abidkulova K. T. Karime; Ozek T. Temel; Baser K. H. C. Kemal Husnu Can; Kovrizhina A. R. Anastasia Ruslanovna; Khlebnikov A. I. Andrey Ivanovich; Damron D. S. Derek; et al. (2016, 2016)
Title screen